The relation between financial statement quality and dividend payout: The role of information asymmetry - 戴怡蕙(Yi-Hui Tai) (Corporate Management Review, 2020)
Many previous studies in the literature have explored how the quality of financial statements affects a company's financing and investing decisions, but few have discussed the impact of the quality of financial statements on dividend policy. Therefore, this article explores the relation between the quality of financial statements and dividends payout and this paper defines the quality of financial statements by the following three items: (1) the level of accruals management; (2) the level of real earnings management; and (3) accruals quality. We further use ＂control-cash flow right deviation of ultimate controllers＂ and ＂adoption of IFRS＂ to proxy information asymmetry and examine whether information asymmetry will influence the relation between the quality of financial statements and the dividend payout. This study employs TWSE/TPEx listed companies from 2010 to 2015 as research samples. The empirical results show that if the quality of financial statements is defined by the level of accruals management, then the worse the quality of financial statements, the higher the ratio of dividend payout. However, if the quality of financial statements is defined by the level of real earnings management or accruals quality, then there is no relation between the quality of financial statements and the ratio of dividend payout. The study also finds that if the level of information asymmetry of companies is larger, the relation between the quality of financial statement and dividend payouts is more pronounced. In other words, The larger the control-cash flow right deviation of ultimate controllers or before adoption of IFRS, the more pronounced relation between the quality of financial statements and the ratio of dividend payout. The results of this research serve as a supplement to the literature as well as a reference for TWSE/TPEx listed companies with regard to the distribution of dividends.